2-Local derivations on finite-dimensional semi-simple Lie algebras - Ayupov, Shavkat; Kudaybergenov, Karimbergen; Sattarovich, Rakhimov Isamiddin (Elsevier, 2015)
We prove that every 2-local derivation on a finite-dimensional semi-simple Lie algebra L over an algebraically closed field of characteristic zero is a derivation. We also show that a finite-dimensional nilpotent Lie algebra L with dim L ≥ 2 admits a 2-local derivation which is not a derivation.